2020
DOI: 10.1108/jstp-04-2020-0077
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing competitive performance of service firms in data-rich environment

Abstract: PurposeThe marketing information system (MkIS) in the data-rich business environment receives all the attention these days, but as essential and perhaps even more essential is the marketing information system management capability (MkISMC). Although many service firms apprehend the return from MkIS, others clearly struggle. It seems that MkIS management capability dynamics and their direct/indirect holistic influence on service firm's competitive performance (SFCP) are unsolved in the current data-driven servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 137 publications
2
22
0
Order By: Relevance
“…In this study, the authors applied both qualitative and quantitative phases initially using the judgemental sampling technique to confirm the model constructs and measurement scales. Judgemental sampling is purposive sampling, where choosing the sample elements is based on the investigators' or experts' judgement that matches the study context (Rahman et al , 2020a). The research model was developed based on the literature review mentioned in the previous section.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the authors applied both qualitative and quantitative phases initially using the judgemental sampling technique to confirm the model constructs and measurement scales. Judgemental sampling is purposive sampling, where choosing the sample elements is based on the investigators' or experts' judgement that matches the study context (Rahman et al , 2020a). The research model was developed based on the literature review mentioned in the previous section.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, the experts and scholars chose 21 categories based on their judgement on the categories of the industries that use software and technology in their regular business activities. This study acknowledged judgemental sampling as purposive sampling, where the selection of sample elements was based on experts' judgement (Rahman et al, 2020b). The experts and academic scholars only included elements that they deem as appropriate for analysing the particular study (Sarstedt et al, 2018).…”
Section: Data Collection and Sample Selection Process For Main Surveymentioning
confidence: 99%
“…The research subordinates communicated the SMEs via the social media connections; of these SMEs, 101 agreed to share their employee contact particulars and give consent to survey their employees. The research subordinates subsequently identified three employees from each SME by considering the contact details of all the employees of the 101 firms via a convenience method similar to that of Rahman et al (2020b). In the convenience sampling technique, the primary consideration was the ease through which the possible respondents could be found or recruited (Baker et al, 2013).…”
Section: Data Collection and Sample Selection Process For Main Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, firms' information system management capabilities are considered the central plethora among industry participants (Yasmin et al, 2020;Peng et al, 2016;Gallego-Gomez et al, 2021). Thus, the present study intends to refer to the view that firms capability of information system management is one of the dominant antecedents that influence the overall competitive performance of firms (Rahman et al, 2020). Based on the above discussion the study investigate the following research question (RQ): RQ1.…”
Section: Introductionmentioning
confidence: 99%